Conceptual Map and World Café: ressignificating the teaching of sciences for the argumentation (Research, Society and Development, 2019)
This article presents proposals for teaching strategies to analyze the use of the Conceptual Map and the World Café, in the classroom and in non - formal environments, as a focus on the students' arguments, involving activities of the Elementary Science discipline. The objective was the insertion of the argumentation through the mentioned strategies with reconstructive questioning of the competences in the processes of teaching and learning. Methodologically, the research provided a qualitative approach, presenting an exploratory and descriptive character, as it familiarized the subjects involved and their concerns, as well as extracting pertinent information during the development of activities in a state school located in the Municipality of Macapá / AP. The research involved twenty-two seventh-year primary school students, ranging in age from eleven to fourteen, fifty-five percent female and forty male. The action pointed to the construction of scientific literacy, as well as made possible the re-signification through the argumentation in the teaching of Sciences. In fact, the strategies have given students considerable change in the subject and contributed to improving students' behavior, argumentation and achievement, making classes dynamic and enjoyable